Pharmacophore modeling for biological targets with high flexibility: LXRβ case study - Sophia Kchouk; Lamees Hegazy (Elsevier, 2022)
Many biological targets are characterized by high binding pocket flexibility posing a challenge in identifying important ligand binding features. Liver X receptors (LXRs) are members of the nuclear hormone receptor super family. Although several X-ray structures for LXRβ bound ligands are available, differences in ligands' binding poses and interactions in the ligand binding pocket causes a challenge in identifying general elements of ligand binding. In this study, we used several LXR X-ray structures and known LXR ligands to study how LXRβ ligands interact with the LXRβ receptor. Using this information, we generated several pharmacophore models that represents important chemical features necessary for LXR binding and activation. Our results show that generating pharmacophore models based on a combined approach of multiple ligands alignments and considering the ligands' binding coordinates yielded the best results. The generated pharmacophore model will be useful for future ligand discovery of LXRβ modulators using virtual screening.